Competitiveness of the broiler industry in Peninsular Malaysia - Benalywa, Zineb Abdulaker M (2019)
Competitiveness has become a highly sought objective across government and private sectors across many nations. At the national level, the importance of competitiveness is significant to maximise the welfare of its population, while the private sector endeavours to be more competitive by increasing profits, value added, return, and market share. Broiler meat appears to be the most popular and the cheapest source of protein in Malaysia, wherein trade protection has the potential to stimulate local industry and enhance food security. The trade competition is undeniably strong and Malaysia has been working towards becoming an essential exporter nation. Nevertheless, this vision is barricaded by several challenges that have been lurking in the industry, apart from the rising cost of production and associated reductions in profitability, taxation, variability of corn and soybean prices, as well as instability of exchange rate. As such, by employing the policy analysis matrix (PAM), as well as the approaches initiated by Balassa and Vollrath, this present study assessed the competitiveness of the broiler industry within the context of Peninsular Malaysia. The PAM was applied to analyse the comparative advantage of broiler production and the impacts of distortions in domestic prices. Revealed comparative advantage (RCA) and relative trade advantage (RTA) were adopted in this study to evaluate the performance of broiler trade. Both primary and secondary data were examined in this study. Secondary data were retrieved from a range of sources, while primary data were gathered from a field survey that involved 310 farmers (contract and non-contract) in Peninsular Malaysia. The study outcomes signified that Malaysia has a robust comparative advantage at all scales of broiler production, particularly amidst contract farmers. The present policy indicators revealed that the broiler industry in Malaysia seems far from being protected. The comparative advantage of the chicken subsector indicated that Malaysia has a relative trade advantage in only a single product group, namely HS020712 (Chickens and Capons, Whole Frozen). As such, this study concludes that despite the increment noted in broiler production, Malaysia appears to depend on import of chickens, regardless whole or cut. Therefore, in order to increase competitiveness, the industry should reduce its reliance on imported feeds, but instead, invest more in developing locally-sourced alternative feeds available to farmers at a lower cost, especially when compared to those imported. It is crucial that both the government and private sectors to promote an integrated broiler contract farming. Provision of incentives by the government to producers in support of the broiler industry is one that is of utmost significant. That being mentioned, a viable policy may be implemented to propose lower exchange rates and tax exemption.